Factores asociados al número de sesiones de fisioterapia en pacientes con tratamiento rehabilitador post accidente de tránsito de un centro médico en Lima, Perú - Ramírez Lupuche, Daniel A. (2025)
Introduction. Traffic accidents are one of the leading causes of physical disability in Peru. Physical therapy plays a key role in restoring functionality, and its duration varies depending on several factors. Identifying these factors could improve therapeutic planning and patient follow-up. Objectives. To determine the number of physical therapy sessions and associated factors in patients undergoing post-traffic accident rehabilitation covered by the Mandatory Traffic Accident Insurance (SOAT). Methods. We conducted a cross-sectional study using records of patients treated in 2022 at a specialized physical medicine and rehabilitation center in Lima, Peru. We included individuals aged ≥18 years covered by SOAT. A quasi-Poisson regression model was used to estimate the number of physical therapy sessions. Results. We analyzed 683 medical records. Of the patients, 67.1% were male, and the median age was 32 years (IQR: 27–41). The lower limb was the most frequently affected region (44.2%), and fractures were the most common type of injury (42.6%). The median number of sessions was 19 (IQR: 10–30); among patients who completed treatment, it was 20. Patients from other regions received 38% fewer sessions than those from Metropolitan Lima (95%CI: 0.39–0.93; p=0.031). Those who underwent post-accident surgery received 30% more sessions (95%CI: 1.16–1.45; p <0.001). Conclusions. Among patients receiving SOAT-covered physical therapy, the median number of sessions was 19, and 20 among those who completed treatment. Surgery and medical re-evaluation were associated with a higher number of sessions, while living outside Lima was associated with fewer sessions.